Studi korelasi kondisi fisik dengan keterampilan bermain futsal - Purwanto, Didik; Murtono, Tri; Liloi, Delvi Kristanti (Jurnal Porkes, 2023)
The aim of this study was to analyze the correlation between physical condition and skills in playing the PJKR futsal club at Tadulako University. This study uses a quantitative method that is correlational with tests and measurements of physical condition and skills in playing futsal. The population of this study were all PJKR Tadulako University club players, totaling 12 people/players. The sample in this study were 12 athletes using the total sampling technique. Data collection techniques in the form of tests and measurements. The instruments used were (1 minute pull up test), (50 meter run), (Illionist agility run), (bleep test) and (sit and reach). The data in the study were analyzed by product moment correlation with the help of SPSS 26. The results showed a significant correlation between physical condition and skills in playing futsal was 91.3%, the remaining 6.7%. The positive correlation results from the analysis that the sig value is 0.004 <0.05. The conclusions of this study are proven by the results of the analysis so that there is a real (significant) relationship between the physical condition variable and the skills variable. From the table it can be seen that f count is 12.541 with a significant/probability level